Current trends in eye diseases and its correlates in an urban population - Agrawal, Deepika; Singh, Jai Veer; Garg, Sunil Kumar; Chopra, Harivansh; Roy, Rupali; Chaturvedi, Manish (Indian Journal of Community Health, 2015)
Background: The trend of ocular diseases in urban areas is changing. Eye diseases due to chronic medical problems are being detected more in urban population. Therefore, there is a need to check for ocular diseases in each age group. Objectives: The study aimed to find the prevalence and causes of ocular morbidity and blindness and their associated factors in urban population. Methods: This study was done in an urban area of Meerut. All the age groups covering 1613 subjects were interviewed and simple torchlight examination of the eyes, followed by testing of vision was done. Results: Prevalence of ocular morbidity was 53.0% and blindness 3.4%. The most common ocular morbidity was refractive error (86.4%), followed by cataract (22.5%) and conjunctivitis (6.0%). The causes of blindness were cataract (72.7%), posterior segment pathologies (20.0%), ocular injury (5.5%) and corneal opacities (1.8%). Both ocular morbidity and blindness were significantly higher in smokers, hypertensives and diabetics. Blindness was more prevalent in alcoholics and in those with history of ocular injury.